THREE NEW SPECIES OF PTEROMALIDAE (HYMENOPTERA : CHALCIDOIDEA) FROM MIDDLE-EAST - NARENDRAN, T.C.; KUMAR, P. GIRISH; SHEEBA, M.; KISHORE, LAMBERT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
Three new species of Pteromalidae viz. Eumacepollus yemensis Narendran sp. nov. Merisomorpha gara Narendran sp. nov. and Hemitrichus longigaster Narendran sp. nov. are described from Yemen. The genera Eumacepolus, Merisomorpha and Hemitrichus are recorded for the first time from Middle-east. Each new species is compared with related species.